TINGKAT KONDISI FISIK EKSTRAKURIKULER CHEERLEADERS (FO RAIDERS) SMP KARTIKA IV-I SURABAYA - HARTONO, ADI (Jurnal Prestasi Olahraga, 2017)
In cheerleading, physical condition, technique mastering, and well-built mental must have been owned by the athletes because those contribute highly in order to gain achievements. Therefore, the goal of this research is important to be completed in order to observe the level of cheerleaders’ physical conditions of FO Raiders cheerleading extracurricular members in yunior haigh school Kartika IV-1 Surabaya. The type of this observation was qualitative descriptive, with approach method of One Shot Model. The chosen research subjects were 20 female students as the members of FO Raiders cheerleaders extracurricular in yunior haigh school Kartika IV-1 Surabaya, with age of 13 – 14 years old. According to the result of the research, it can be concluded that the mean of body weight index is 19,78 kg/m², the mean of the flexibility are 13,85 cm, the mean of balance are 7,94 seconds, the mean of extensor back muscle strength are 45,1 kg, the mean of leg muscle strength are 37,15 kg, the mean of the shoulder muscle’s pushing strength are 16 kg, the mean of the arm muscle strength are 30 times,the mean of the stomach muscle strength are 21 times, the legs’ exploding power are 13,85 inchi, and the enduring power of cardio respiratory vascular are 25,73 ml/kg/mnt.Key words: physical condition, FO Raiders extracurricular cheerleaders yunior haigh school Kartika IV-1 Surabaya